Pengaruh Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Pada Badan Kesatuan Bangsa Dan Politik Kabupaten Majene - Wahyu Maulid Adha; Muhammad Shaleh Z (Fakultas Ekonomi Universitas Indonesia Timur, 2019)
Management of Civil Servants is one of the things contained in the success of achieving the goals of an organization is strongly influenced by the role and performance of its employees. Leadership, motivation, and work discipline are the variables that determine the level of performance. The purpose of this study was to determine the effect of leadership, motivation, and work discipline simultaneously on the performance of employees at the National Unity and Politics Board of Majene Regency. The type of data used in this study is quantitative data with primary data sources and secondary data. In this study the population was all employees of the Office of the National Unity and Politics of Majene Regency, amounting to 27 people. Data collection techniques in this study used observation, questionnaire, and documentation techniques. The data analysis technique of this study used multiple linear regression analysis, coefficient of determination, simultaneous test (F test), and partial test (t test). Based on the simultaneous test statistical table, the test results show that the significant value of Fcount 177.233 is greater than the Ftable value of 2.960 with a significance level of F of 0.000 which is less than 0.05, thus Leadership (X1), Motivation (X2) and Discipline (X3) significant effect on performance in the National Unity and Politics Agency Majene Regency. Based on the Table of coefficient of determination, shows that the R Square value of 0.612 means 61.2% The three independent variables Leadership (X1), Motivation (X2) and Discipline (X3) together can explain the model of this study